AGRONOMIC AND ECONOMIC ANALYSIS OF LOWLAND RICE CULTIVATION USING THE INTEGRATED CROP AND LAND MANAGEMENT APPROACH - Munawwarah, Tarbiyatul - (Jurnal Agroekoteknologi Tropika Lembab, 2024)
The research investigated the implementation of Integrated Crops and Land Management (ICLM) model, a holistic farming approach combining various technological elements to enhance productivity. Conducted from April to September 2022 in Bhuana Jaya Village, Tenggarong Seberang Sub-District, Kutai Kartanegara Regency, East Kalimantan Province, on an 8-hectare site, the research focused on key components: utilization of superior rice varieties (Mekongga, Cakrabuana Agritan, and Ciherang Janger), spaced planting methodology (Jajar Legowo), and a balanced fertilization approach encompassing chemical, organic, soil conditioner, and biological fertilizers (50 kg Urea, 300 kg NPK Phonska, 400 kg Petroganik, 10 kg Antazam, and 10 kg Petrobio ha-1, respectively). Liquid Organic Biofertilizer (LOB) were introduced at a rate of 10-20 liters ha-1. The research assessed vital parameters such as plant height, tiller count, panicle length, branch number per panicle, panicle weight, and rice productivity. Statistical analyses included t-tests for plant response and F-tests to evaluate the model's impact on productivity. Economic viability was gauged using the Benefit-Cost (B/C) ratio. The findings revealed substantial productivity gains: 4.13-6.03 t MDG ha-1 (Mekongga), 7.02 t MDG ha-1 (Cakrabuana Agritan), and 7.85 t MDG ha-1 (Ciherang Janger). Moreover, the economic analysis resulted in a favorable ratio of 2.15, indicating the model's financial viability or increased by 69-73%.